Hasil Belajar Kewirausahaan Ditinjau Dari Cara MengajarDosen Dan Minat Berwirausaha Mahasiswa Pada MahasiswaPendidikan Akuntansi Fakultas Keguruan Dan IlmuPendidikan Universitas Muhammadiyah Surakarta Angkatan Tahun 2013 - Cahyaningsih, Novia; , Drs. Nur Chusni. M,Ag (2016)
The aims of this study are to determine: 1) Contributionsin the way of lecturing towards Entrepreneurship learning outcomes, 2) Contributions of student'sinterest in entrepreneurship to the learning outcomes of Entrepreneurship, 3) Contributions between the way of lecturing and student's interest towardsEntrepreneurship learning outcomes. This type of research is quantitative associative. The population in this study are students of Muhammadiyah University of Surakarta in accounting education force in 2013, the amount of the students are 183 students, with 119 samples taken with using proportional random sampling. Data collection techniques used is questionnaire that has been tested by validity and reliability testing. The techiques of data analysis used are multiple regression, t-test, F-test, the effective contribution and relative contribution. The conclusion that can be drawn from this study are: 1) There is a significant relationship between the learning outcomes of entrepreneurship by t-test is obtained from tcount> ttable, 2.712> 1.981 and significant value <0.05 is 0.025. 2) There is a significant effect between interest in entrepreneurship students to the learning outcomes of entrepreneurship by t-test obtained tcount> ttable, namely 5.747> 1,981 and significant value of 0.05 is 0.025. 3) There is a significant relationship between the way of lecturing and student's interest in entrepreneurship to entrepreneurial learning outcomes based on those F-test known by Fcount> Ftabel, 70.474> 3.074 with the significant value of 5%. The calculation result of R2 obtained 54.9% of entrepreneurial learning outcomes are influenced by the way of lecturingand student's interest in entrepreneurship, the remaining 45.1% is influenced by the other variables which are not examined in this study.